The complete mitochondrial genome of black sea bass, Centropristis striata. Issue 2 (2nd April 2020) - Li, Weiye; Liu, Minhai; Zhang, Xiaolin; Xu, Zhijin; Xiaolong, Yin; Fu, Rongbing; Jiang, Xiamin
Abstract: The complete mitochondrial genome was sequenced from the marine teleost fish Black Sea Bass, Centropristis striata . The genome sequence is 16, 986 bp in size and has a base composition of A (26.65%), T (26.44%), C (28.63%), and G (18.28%). The phylogenetic analysis showed that C. striata belongs to Serranidae family and is most closely related to Hypoplectrus . The complete mitochondrial genome sequences provided here was the first one in Centropristis, which would be useful for further understanding the evolution and conservation genetics of C. striata .